2022
DOI: 10.1155/2022/4774195
|View full text |Cite|
|
Sign up to set email alerts
|

A Meta-Analysis of How Nonalcoholic Fatty Liver Disease Affect Antiviral Treatment of Patients with e Antigen-Positive Chronic Hepatitis B

Abstract: Background. Nonalcoholic fatty liver disease (NAFLD) and chronic hepatitis B (CHB) are both the most common underlying diseases leading to cirrhosis and hepatocellular carcinoma, and NAFLD and HBV infection are the first and second leading causes of chronic liver disease in China. However, there are still a lot of controversies about whether the combined presence of CHB and NAFLD will affect the course or outcome of liver disease together with HBV, and how the two affect each other. Objective. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%